Multicolor fluorescence imaging using a single RGB-IR CMOS sensor for cancer detection with smURFP-labeled probiotics - Oh, Gyungseok; Cho, Hong Jun; Suh, SeungBeum; Ji, Yuhyun; Chung, Hak Suk; Lee, Deukhee; Kim, Keri (The Optical Society, 2020)
A multicolor fluorescence imaging device was recently developed for image-guided surgery. However, conventional systems are typically bulky and function with two cameras. To overcome these issues, we developed an economical home-built fluorescence imaging device based on a single RGB-IR sensor that can acquire both color and fluorescence images simultaneously. The technical feasibility of RGB-IR imaging was verified ex vivo in chicken breast tissue using fluorescein isothiocyanate (FITC), cyanine 5 (Cy5), and indocyanine green (ICG) as fluorescent agents. The minimum sensitivities for FITC, Cy5, and ICG were 0.200 mu M, 0.130 mu M, and 0.065 mu M, respectively. In addition, we validated the fluorescence imaging of this device in vitro during a minimally invasive procedure using smURFP-labeled probiotics, which emit a spectrum similar to that of Cy5. Our preliminary study of the ex vivo tissue suggests that Cy5 and ICG are good candidates for deep tissue imaging. In addition, the tumor-specific amplification process was visualized using cancer cells incubated with probiotics that had been labeled with a fluorescent protein. Our approach indicates the potential for in vivo screening of tumors in rodent tumor models. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement